A RESEARCH ON ROUTING PROTOCOLS AND SECURITY OF CHALLENGES IN MANETs - Rajshree Saxena & Dr. Raghav Mehra (International Journal of Research Science and Management, 2017)
The procession in the area of internet due to wireless networking technologies gives rise to multiple new applications. In the past few decades, we have found many advance developments in wireless networks. With these developments and large number of applications that are being provided by MANETs, we still face some challenges that have to be overcome. The baseless and active nature of these networks demand new set of networking schemes that should be implemented to provide effective peer-to-peer communication. MANETs hire traditional TCP/IP structure to provide this peer-to-peer communication between nodes in the network. An important interesting research area in MANET is “Routing”. This Routing is not only a very challenging task but also has received a rattling amount of attention from researches. Because of lack of a defined central authority, security of the routing process becomes a challenging task thereby leaving MANETs vulnerable to attempt, which results in declension in the performance as well as raises a serious question about the dependability of these such networks. In this paper, we are providing the history of MANET, challenges that are being involved in MANET and an overview of a spacious range of routing protocols proposed. We are also providing the known routing attacks and many of the proposed measures to these attacks in multiple works.